Analytical and numerical studies for slip flows of a generalised Phan‐Thien–Tanner fluid. Issue 3 (24th January 2020) - Ribau, A. M.; Ferrás, L. L.; Morgado, M. L.; Rebelo, M.; Afonso, A. M.
Abstract: This work presents analytical and numerical studies for pure Couette and combined Poiseuille‐Couette flows under slip. The fluid behaviour is described by the recently proposed viscoelastic model, known as the generalised simplified Phan‐Thien‐Tanner constitutive equation, that considers the Mittag‐Leffler function instead of the classical linear and exponential functions of the trace of the stress tensor, and provides one or two new fitting constants in order to achieve additional fitting flexibility. The solutions derived in this work allow a better understanding of the model and its influence on the slippery behaviour of some complex fluids, contributing in this way to improve the modeling of complex fluids. Abstract : This work presents analytical and numerical studies for pure Couette and combined Poiseuille‐Couette flows under slip. The fluid behaviour is described by the recently proposed viscoelastic model, known as the generalised simplified Phan‐Thien‐Tanner constitutive equation, that considers the Mittag‐Leffler function instead of the classical linear and exponential functions of the trace of the stress tensor, and provides one or two new fitting constants in order to achieve additional fitting flexibility….